The Power of Silence: Jan Skácel, the Banned Man - Belia, Marta (2023)
Jan Skácel is a Czech poet whose literary production marked the second half of the 20th century, aparticularly difficult historical period. In 1948 the Communist Party had implemented a coup d’état thus conquering the totalitarian management of power and had begun to accentuate the ideological control of cultural life. After a short period of more relaxed censorship, in 1968 the harsh period of the so-called “normalization” began: in 1970 Skácel was banned from publishing. In the decade of ban on official publishing he never left his country and never stopped writing verses, declaring his suffering, and tirelessly denouncing, often using refined figures of speech, the difficult condition of the poet reduced to silence. This article proposes an analysis of these texts following some thematic nuclei: first the poems which contain metaphors drawn from the animal world used to represent the figure of the banned poet will be analyzed, to then examine the compositions in which Skácel more explicitly and directly denounces the censorship.
Keywords: Czech poetry; normalization; censorship; totalitarian regime; Czechoslovakia; Central Europe